Chemical and biological attributes of a lowland soil affected by land leveling - Parfitt, José Maria Barbat; Timm, Luís Carlos; Reichardt, Klaus; Pinto, Luiz Fernando Spinelli; Pauletto, Eloy Antonio; Castilhos, Danilo Dufech (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the relationship between soil chemical and biological attributes and the magnitude of cuts and fills after the land leveling process of a lowland soil. Soil samples were collected from the 0–0.20 m layer, before and after leveling, on a 100 point grid established in the experimental area, to evaluate chemical attributes and soil microbial biomass carbon (MBC). Leveling operations altered the magnitude of soil chemical and biological attributes. Values of Ca, Mg, S, cation exchange capacity, Mn, P, Zn, and soil organic matter (SOM) decreased in the soil profile, whereas Al, K, and MBC increased after leveling. Land leveling decreased in 20% SOM average content in the 0–0.20 m layer. The great majority of the chemical attributes did not show relations between their values and the magnitude of cuts and fills. The relation was quadratic for SOM, P, and total N, and was linear for K, showing a positive slope and indicating increase in the magnitude of these attributes in cut areas and stability in fill areas. The relationships between these chemical attributes and the magnitude of cuts and fills indicate that the land leveling map may be a useful tool for degraded soil recuperation through amendments and organic fertilizers.